Akibat Hukum Dari Wanprestasi Yang Dilakukan Franchisee Kepada Franchisor 612 /Pdt.G./2017/PN Jkt.Sel. - Handono, Bintang Sabrina; Urbanisasi, Urbanisasi (Peneliti.net, 2023)
This study aims to find out the reasons for default by the franchisee to the franchisor. Franchisee or what is often known as franchising is a way of cooperation in the field of business between two or more companies, where one party will act as the franchisor and the other party is called the franchisee. In the process, the franchisor grants a license to the franchisee to participate in the distribution of goods and services on behalf of the franchisor in the agreed area, then the business carried out by the franchisee must follow the procedures and procedures set by the franchisor in which the franchisor provides assistance to the franchisee. Where in return, the franchisee pays an initial fee or royalties. This study uses a normative legal research method which explains it using the Criminal Code regarding default. From this research, there are results found. The first result is that in the initial evidence and lawsuit the plaintiffs are correct that no royalties were given to the central company. Then, there is evidence in the form of witnesses and videos showing that what was done could be wrong and right. Thus, it can be said that a prospective company must take care to prevent unwanted things from happening. Based on this, it can be said that the plaintiff is in default and of course has harmed the defendant